A novel mutation in FNIP1 associated with a syndromic immunodeficiency and cardiomyopathy - Ilia Spivak; Atar Lev; Amos J. Simon; Ortal Barel; Ido Somekh; Raz Somech (Immunogenetics, 2025)
Genetic variants in Folli culin inte racting protein 1 (FNIP1) were recently discovered as monogenic causes for immunodeficiency and cardiomyopathy, with only a few patients diagnosed thus far. In this study, we describe a patient harboring a novel genetic variant in FNIP1 causing immunodeficiency with cardiac involvement. Clinical and immunological workups were performed. Genetic evaluation utilizing whole-exome sequencing (WES) and Sanger sequencing was conducted. The index patient (subject II-4) presented with hypertrophic cardiomyopathy, recurrent infections, and chronic diarrhea during infancy. Immune workup revealed agammaglobulinemia and a lack of B lymphocytes. Genetic evaluation identified a homozygous 13-bp duplication variant in FNIP1 (c.52_64dupGCGCCCGGCCGCG, p. Asp22GlyfsTer21) resulting in a frameshift in exon 1/18. She was treated with supplemental intravenous immunoglobulins (IVIg) with good control of sinopulmonary and gastrointestinal manifestations. Her sibling (subject II-1) had similar clinical features, along with dysmorphic facial features and hypotony, and succumbed to cardiogenic shock at the age of 2 months, prior to genetic evaluation. Diagnosis of novel immunodeficiencies promotes our understanding of the immune system, enabling genetic counseling as herein, and may assist in the development of novel medical therapies in the future. FNIP1 loss-of-function should be considered in patients presenting in infancy with cardiac manifestations along with agammaglobulinemia (and B-cell lymphopenia).

B cell repertoire in patients with a novel BTK mutation: expanding the spectrum of atypical X-linked agammaglobulinemia - Ori Toker; Arnon Broides; Atar Lev; Amos J. Simon; Orli Megged; Oded Shamriz; Yuval Tal; Raz Somech; Yu Nee Lee; Amit Nahum (Immunologic Research, 2022)

Exploring genetic defects in adults who were clinically diagnosed as severe combined immune deficiency during infancy - Ido Somekh; Atar Lev; Ortal Barel; Yu Nee Lee; Ayal Hendel; Amos J. Simon; Raz Somech (Immunologic Research, 2021)

A novel zeta-associated protein 70 homozygous mutation causing combined immunodeficiency presenting as neonatal autoimmune hemolytic anemia - Eduard Ling; Arnon Broides; Galina Ling; George Shubinsky; Nurit Hadad; Amit Nahum; Amos J. Simon; Atar Lev; Raz Somech (Immunologic Research, 2021)

Immune reconstitution after HSCT in SCID—a cohort of conditioned and unconditioned patients - Uri Manor; Atar Lev; Amos J. Simon; Daphna Hutt; Amos Toren; Bella Bielorai; Lior Goldberg; Tali Stauber; Raz Somech (Immunologic Research, 2019)

MHC II deficient infant identified by newborn screening program for SCID - Nufar Marcus; Tali Stauber; Atar Lev; Amos J. Simon; Jerry Stein; Arnon Broides; Ido Somekh; Shlomo Almashanu; Raz Somech (Immunologic Research, 2018)

Co-appearance of OPV and BCG vaccine-derived complications in two infants with severe combined immunodeficiency - Sophia Heiman; Merav Weil; Lester M. Shulman; Amos J. Simon; Atar Lev; Raz Somech; Tali Stauber (Immunologic Research, 2018)

The clinical and laboratory spectrum of dedicator of cytokinesis 8 immunodeficiency syndrome in patients with a unique mutation - Arnon Broides; Amarilla B Mandola; Jacov Levy; Baruch Yerushalmi; Vered Pinsk; Michal Eldan; George Shubinsky; Nurit Hadad; Rachel Levy; Amit Nahum; Miriam Ben-Harosh; Atar Lev; et al. (Immunologic Research, 2017)

Combined immunodeficiency in a patient with mosaic monosomy 21 - Erez Rechavi; Sarina Levy-Mendelovich; Tali Stauber; Jana Shamash; Shlomit Reinstein; Helly Vernitsky; Dganit Adam; Amos J. Simon; Atar Lev; Annick Raas-Rothschild; Raz Somech (Immunologic Research, 2016)

Highlighting the problematic reliance on CD18 for diagnosing leukocyte adhesion deficiency type 1 - Sarina Levy-Mendelovich; Erez Rechavi; Omar Abuzaitoun; Helly Vernitsky; Amos J. Simon; Atar Lev; Raz Somech (Immunologic Research, 2016)

Insight into normal thymic activity by assessment of peripheral blood samples - Diti Machnes-Maayan; Atar Lev; Uriel Katz; David Mishali; Amir Vardi; Amos J. Simon; Raz Somech (Immunologic Research, 2015)

Purine nucleoside phosphorylase deficiency presenting as severe combined immune deficiency - Raz Somech; Atar Lev; Galia Grisaru-Soen; Shelly I. Shiran; Amos J. Simon; Eyal Grunebaum (Immunologic Research, 2013)